2020
DOI: 10.1109/access.2020.2974783
|View full text |Cite
|
Sign up to set email alerts
|

Soft Sensor Modeling for Unobserved Multimode Nonlinear Processes Based on Modified Kernel Partial Least Squares With Latent Factor Clustering

Abstract: To cope with the soft sensor modeling of unobserved multimode nonlinear processes, this paper proposes a modified kernel partial least squares (KPLS) by integrating latent factor clustering (LFC), called LFC-KPLS. In the proposed method, the process data are first divided into several batches orderly, and then projected onto the latent space by using the nonlinear functional expansion technology. In the latent space, partial least squares method is applied to compute the regression coefficients between the inp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…19 Wang et al ( 2019) used a self-organized framework to construct multiple KPLS models and used conditional probability density analysis to identify the sample mode. 20 Deng et al (2020) proposed a modified KPLS method that uses latent factors and identified sample modes using Bayesian inference. 21 Wu et al (2021) proposed a locality preserving randomized canonical correlation analysis method for real-time nonlinear process monitoring.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…19 Wang et al ( 2019) used a self-organized framework to construct multiple KPLS models and used conditional probability density analysis to identify the sample mode. 20 Deng et al (2020) proposed a modified KPLS method that uses latent factors and identified sample modes using Bayesian inference. 21 Wu et al (2021) proposed a locality preserving randomized canonical correlation analysis method for real-time nonlinear process monitoring.…”
Section: Introductionmentioning
confidence: 99%
“…20 Deng et al (2020) proposed a modified KPLS method that uses latent factors and identified sample modes using Bayesian inference. 21 Wu et al (2021) proposed a locality preserving randomized canonical correlation analysis method for real-time nonlinear process monitoring. 22 Zhang et al (2021) investigated a mixture of probabilistic PCA with clustering for process monitoring.…”
Section: Introductionmentioning
confidence: 99%